Pengaruh dan Kepentingan Stakeholder dalam Pengelolaan Lingkungan Pertambangan Pasir Sungai Saddang Kabupaten Pinrang Sulawesi Selatan - Arsyad, Arsyad; Arifin, M. Aris; Jamaluddin, Jamaluddin; Hamzah, Hamzah; Reno, Reno; Rukmana, D.; Salman, D.; Alimuddin, I. (Universitas Hasanuddin, 2025)
Saddang River sand mining has quite an enormous economic potential in the form of direct and indirect economic benefits for the community around the mining area. This significant economic potential attracts various parties to be involved in managing the Saddang River sand mining. The stakeholders involved have their respective influences and interests. Research was conducted to find out the stakeholders involved and their respective concerns. Focus Group Discussions, in-depth interviews, and field surveys were conducted. The research results show that if the interests of local communities related to river sand mining activities are met, they will use their positive influence to support Saddang River sand mining activities. However, if the interests of local communities related to river sand mining activities are unmet or tend to be ignored, then local communities will tend to exert a negative influence on river sand mining activities. In this way, Saddang River sand mining can be managed sustainably. If the legality of Saddang River sand mining is fulfilled, the protection of local community interests will be considered, and environmental protection will not be neglected.